1981
DOI: 10.1111/j.2044-8295.1981.tb02194.x
|View full text |Cite
|
Sign up to set email alerts
|

Can passive touch be better than active touch? A comparison of active and passive tactile maze learning

Abstract: In a comparison of the performance of active (n = 15) and passive (n = 15) mechanically yoked subjects who learned their way through a tactile maze, it was shown that active subjects made more errors and took a greater number of trials to reach criterion than did passive subjects. In addition, the difference between active and passive performance was largely accounted for by the greater number of repeated errors made by active subjects. In a second experiment it was found that the poorer performance of active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 3 publications
0
25
0
3
Order By: Relevance
“…Interestingly, similar controversial results can also be WU AND LIN Psychology & Marketing DOI: 10.1002/mar found in empirical studies of control and life quality (Burger, 1989;Mills, 1979;Richardson et al, 1981;Schulz, 1976;. Shapiro et al proposed the concept of "match" to explain the controversial results (Evans et al, 1993;Shapiro et al, 1996).…”
Section: Information Controlmentioning
confidence: 75%
See 1 more Smart Citation
“…Interestingly, similar controversial results can also be WU AND LIN Psychology & Marketing DOI: 10.1002/mar found in empirical studies of control and life quality (Burger, 1989;Mills, 1979;Richardson et al, 1981;Schulz, 1976;. Shapiro et al proposed the concept of "match" to explain the controversial results (Evans et al, 1993;Shapiro et al, 1996).…”
Section: Information Controlmentioning
confidence: 75%
“…Because these resources are limited in the working memory, and people perform two tasks simultaneously when given information control (i.e., seeking target information and information control), the cognitive resources of information processing are reduced (Broadbent, 1971;March, 1978;Treisman, 1969). Therefore, the performance of information processing should deteriorate due to information control (Richardson, Wuillemin, & McKintosh, 1981).…”
Section: Information Controlmentioning
confidence: 99%
“…N. Wilson, Foreman, Gillett, & Stanton, 1997) have found no difference between active and passive participants. Finally, in studies on searching for structure in 3D data (Marchak & Zulager, 1992) and tactile maze learning (Richardson, Wuillemin, & MacKintosh, 1981), participants who were given active control were found to perform worse than passive participants. Even within a single study, different comparisons of active and passive conditions have sometimes produced apparently contradictory results (Attree et al, 1996;Christou & Bülthoff, 1999;P.…”
Section: Previous Findings On Interactivitymentioning
confidence: 99%
“…For example, in a mazelearning study, Richardson et al (1981) found that participants who were required to define their pattern of maze learning and to play the game performed worse than those who only played the game; apparently, handling two challenging tasks concurrently exceeded available cognitive resources and diminished performance. Along the same lines, customers perform two tasks in an SST process: (1) they cognitively comprehend the content and consequences of service choices, such as the terms and charges of a service delivery, and (2) they behaviorally manage the sequence of message navigation and configure the service procedure to achieve their desired outcomes.…”
Section: Effects Of Combined-feature Designmentioning
confidence: 97%